The Emerging Roles of Pericytes in Modulating Tumor Microenvironment - Sun, Ruipu; Kong, Xiangzhan; Qiu, Xiaoyi; Huang, Cheng; Wong, Ping-Pui (Frontiers in Cell and Developmental Biology, 2021)
Pericytes (PCs), known as mural cells, play an important blood vessel (BV) supporting role in regulating vascular stabilization, permeability and blood flow in microcirculation as well as blood brain barrier. In carcinogenesis, defective interaction between PCs and endothelial cells (ECs) contributes to the formation of leaky, chaotic and dysfunctional vasculature in tumors. However, recent works from other laboratories and our own demonstrate that the direct interaction between PCs and other stromal cells/cancer cells can modulate tumor microenvironment (TME) to favor cancer growth and progression, independent of its BV supporting role. Furthermore, accumulating evidence suggests that PCs have an immunomodulatory role. In the current review, we focus on recent advancement in understanding PC’s regulatory role in the TME by communicating with ECs, immune cells, and tumor cells, and discuss how we can target PC’s functions to re-model TME for an improved cancer treatment strategy.